IoT-based Pregnant Mother Contraction Monitoring System Design - Romadhoni, Sahrul; Sulistiyowati, Indah; Rizqiyah, Mar'ati Amalia (Jurnal Edukasi Elektro, 2024)
Pregnancy is an important stage in a woman's life that requires special monitoring and care to ensure the well-being of both mother and fetus. The presence of uterine contractions is an im-portant indicator of imminent labour, and prompt monitoring is essential to spot difficulties and ensure a safe delivery. This study aims to track contractions in pregnant women to improve pre-natal and labour care. Real-time monitoring, recording and analysis of uterine contractions. This research is a type of R&D research with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation. The result of this tool is that it can precisely track contraction activity and send information to the IoT network. Through an easy-to-use mobile app, this in-formation can be accessed by medical staff caring for pregnant women and pregnant women themselves. To provide continuous monitoring, provide early notification of alarming changes, and facilitate rapid medical response, this monitoring system utilizes IoT technology. This can ease the burden on medical institutions, lower the possibility of difficulties during labour, and provide a sense of security for pregnant women. As an innovative and effective tool, the Inter-net of Things-based Maternal Contraction Monitoring System is anticipated to improve prenatal and delivery healthcare, reduce maternal and infant mortality, and monitor contractions in preg-nant women. The healthcare of pregnant women around the world could be significantly im-proved with the successful implementation of this approach.